1998
DOI: 10.1159/000014036
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Activating Factor Levels in Term and Preterm Human Milk

Abstract: It is well known that necrotizing enterocolitis (NEC) is less frequent in newborns being fed human breast milk. Since recent studies indicated that platelet-activating factor (PAF) plays an important role in pathogenesis of NEC, this study was conducted to investigate the PAF levels in human milk. Colostrum and mature human milk (samples obtained in the third week) of three groups of mothers were investigated. The first group had given birth within less than 32 weeks, the second between 33–37 weeks and the thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Research looking at a gut-stimulation, or gut-priming protocol has demonstrated potential benefits of promoting maturation of the gut by introducing early feedings with human milk [3] . The activity of acetyl hydrolase (PAF-AH), an enzyme that degrades PAF, is lower in neonates under 3 wk of age than at any other time [145,146] . The additional presence of PAF-AH activity may also partly explain the protective effect of breast milk, as infant formulas do not contain it [8] .…”
Section: Human Milkmentioning
confidence: 99%
“…Research looking at a gut-stimulation, or gut-priming protocol has demonstrated potential benefits of promoting maturation of the gut by introducing early feedings with human milk [3] . The activity of acetyl hydrolase (PAF-AH), an enzyme that degrades PAF, is lower in neonates under 3 wk of age than at any other time [145,146] . The additional presence of PAF-AH activity may also partly explain the protective effect of breast milk, as infant formulas do not contain it [8] .…”
Section: Human Milkmentioning
confidence: 99%
“…Factors thought to be important in the reduction of NEC in infants fed human milk include secretory immunoglobulin A, epidermal growth factor, and platelet activating factor-acetylhydrolase. [5][6][7] Other benefits of human milk for the preterm infant, although not as dramatic, warrant attention. Human milk may have a significant impact on the growth of the central nervous system.…”
mentioning
confidence: 99%
“…Initially, it was believed that the main function of PAF was limited to the stimulation of platelet aggregation and expansion (dilation) of blood vessels. 47 It is currently apparent that PAF, through receptors located on numerous cells of the immune system, affects the course of inflammation. It has been established that this factor can modulate the production of mediators such as prostaglandins, cytokines, and other inflammatory factors.…”
Section: Paf and Food Anaphylaxismentioning
confidence: 99%
“…It targets cells through specific receptors (PAF receptor). Initially, it was believed that the main function of PAF was limited to the stimulation of platelet aggregation and expansion (dilation) of blood vessels 47 . It is currently apparent that PAF, through receptors located on numerous cells of the immune system, affects the course of inflammation.…”
Section: Paf and Food Anaphylaxismentioning
confidence: 99%